Triterpenes and saponins from Rudgea viburnioides - Young, M. Claudia M.; Araújo, Angela Regina [UNESP]; Da Silva, Cristhiane A. [UNESP]; Lopes, Márcia Nasser [UNESP]; Trevisan, Ligia M. V. [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (American Chemical Society (ACS), 1998)
A novel triterpene; viburgenin (1), has been isolated from an extract of the ripe fruit rinds of Rudgea viburnioides, together with the known saponins, arjunglucoside I and trachelosperosides B-1 and E-l, and the triterpenes trachelosperogenin B (2) and arjungenin. Compound 2 was previously obtained as a product from enzymatic hydrolysis, and it is reported for the first time as a natural product. The structure of compound 1 was determined as 2α,3β,19α,23,24-pentahydroxyurs-12-ene by extensive use of 1D and 2D NMR spectroscopic methods. Compound 1 exhibited moderate antifungal activity against Cladosporium cladosporioides.
Keywords: miconazole; nystatin; saponin; trachelosperogenin b; triterpene; unclassified drug; viburgenin; antifungal activity; bioassay; brazil; cladosporium; drug isolation; fruit; hydrolysis; mass spectrometry; nonhuman; nuclear magnetic resonance spectroscopy; Antifungal Agents; Brazil; Chromatography, Thin Layer; Cladosporium; Magnetic Resonance Spectroscopy; Mass Spectrometry; Microbial Sensitivity Tests; Plants, Medicinal; Saponins; Spectrophotometry, Infrared; Spectrophotometry, Ultraviolet; Triterpenes; Cladosporium cladosporioides; Rudgea; Rudgea viburnioides